Is the Environmental-Economic Performance Relationship Symbiotic? Evidence from Listed Non-Financial Firms in Nigeria - Mohammed Kayode Ajape; V. Santi Paramita (Universitas Pasundan, 2023)
This study aims to examine whether environmental sustainability disclosure (ESD) connects symbiotically with the economic performance of non-financial listed firms in Nigeria. The study employed ex-post facto design by collecting secondary data on return on equity (ROE) and measures of ESD from annual financial reports of eighty-six (86) listed non-financial firms with environmentally significant operational impact in Nigeria. Descriptive statistics, including mean and standard deviation were used to describe the properties of the data while the Granger causality test was applied to test the stated hypothesis. The results indicate the existence of a bi-directional association between the measures of ESD and economic performance. Thus, it portrays the economic consequence of listed firms’ operations. The study took a detour from examining mere relationships to delve into causality and thus, implies that commitment to ESD presage benefits to both the host communities and firms. The value of the study lies in the fact that it disentangled the question of causality between ESD and the economic performance of listed non-financial firms in Nigeria. Therefore, within the Nigerian context, the study is pioneer evidence of symbiotic relations between ESD and ROE and hence, improves sustainability discourse.